2003
DOI: 10.1210/jc.2003-030158
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Levels and Blood Pressures in Nondiabetic Adolescent Females

Abstract: Adiponectin is an adipose-derived plasma protein. Recently the plasma adiponectin levels have been linked to most variables of metabolic syndrome (MS) and risk factors of coronary artery disease (CAD). However, its relation with blood pressure is yet unclear. Here we report the relationship between the plasma adiponectin levels and blood pressures in 68 female adolescents (age 16.1 +/- 1.8 yr). We found that the plasma adiponectin levels correlated significantly with both the systolic blood pressure (SBP) (gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 29 publications
3
41
0
1
Order By: Relevance
“…36 In contrast, an inverse association between adiponectin and SBP independent of BMI was shown in healthy Taiwanese female adolescents. 12 In our study, after adjusting for various indirect (BMI/ waist circumference) and direct (%TF/percent body fat) adiposity measures as well as IR (HOMA), we found that adiponectin was negatively associated with SBP in male Chinese adolescents.…”
Section: Association Of Leptin With Adiponectinmentioning
confidence: 47%
See 1 more Smart Citation
“…36 In contrast, an inverse association between adiponectin and SBP independent of BMI was shown in healthy Taiwanese female adolescents. 12 In our study, after adjusting for various indirect (BMI/ waist circumference) and direct (%TF/percent body fat) adiposity measures as well as IR (HOMA), we found that adiponectin was negatively associated with SBP in male Chinese adolescents.…”
Section: Association Of Leptin With Adiponectinmentioning
confidence: 47%
“…10 Limited data on adipokines and blood pressure (BP) exist for adolescents, especially in a relatively lean Chinese population. 11,12 As compared with adulthood, adolescence is a period of rapid physical growth and functional maturation, accompanied by growing gender differences in anthropometric measurements, BP, body composition, hormones and metabolism. Decreased insulin sensitivity in puberty (pubertal insulin resistance (IR)) is a well-observed phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…After adjustment for confounding factors, the association still remained significant between SBP and adiponectin, but not between DBP and adiponectin. 14 Recently, Sung et al 12 in their communitybased survey of 2045 residents aged X40 years found that adiponectin was independently associated with SBP and DBP in a subgroup of their 1512 non-diabetic, non-hypertensive population.…”
Section: Introductionmentioning
confidence: 99%
“…13 The biological mechanisms responsible for the association of the reduced adiponectin level with higher blood pressure are not known at present 5 and the specific biological role of adiponectin still awaits clarification. 14 It is possible that only under metabolic or cellular stress conditions is a reduction or a lack of adiponectin associated with deleterious consequences. 5 Most of the studies examining adiponectin and blood pressure have been conducted in hypertensive or diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] These observations suggest that adiponectin might be a useful biomarker for management of metabolic disorders. Evidence also indicates that adiponectin has beneficial effects on insulin resistance, 16 endothelial function, hypertension, [17][18][19] ischemic heart disease, and atherosclerosis. 20,21 Adiponectin may, therefore, be a key determinant of the development of metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%